REPRESENTASI KRITIK SOSIAL DALAM FILM WARKOP DKI JANGKRIK BOSS PART 1 (2016) : ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE - Ikrar Yuharto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Films serve not only as entertainment, but also as a medium for conveying social criticism. Their messages are often implied, especially when wrapped in the comedy genre. This study aims to describe the representation of social criticism contained in the film Warkop DKI Reborn: Jangkrik Boss! Part 1 using a descriptive qualitative method and Charles Sanders Peirce's semiotic analysis. Data was collected through non-participant observation and documentation of relevant scenes and dialogues. The analysis identified 14 scenes that significantly represent social criticism, with a dominance of issues related to bureaucratic concerns such as corruption and abuse of power (7 scenes). Additionally, the film highlights criminal issues, ranging from street crime to white-collar crime (5 scenes), as well as various forms of societal norm violations (2 scenes). In conclusion, the film successfully wraps social issues in a comedic package, making it not only entertaining but also an effective social mirror encouraging viewers to reflect on social realities